(untitled) - Toynbee, Arnold (New York, 1948)
Arnold Toynbee's A Study of History is a six-volume analysis of the rise and fall of human civilizations
Keywords: History,Lịch sử,Civilization,Văn minh; Philosophy,Lý luận